PERAN PERGURUAN TINGGI DI ERA REVOLUSI INDUSTRI 4.0 - Fahrina Yustiasari Liriwati; Rulitawati Rulitawati; Zulhimma Zulhimma (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The Industrial Revolution 4.0 has begun to drip various aspects of life, and social order. The world of national education has no choice but to respond to these challenges. The Industrial Revolution 4.0 was the fourth industrial revolution and came after the first industrial revolution with the discovery of a steam engine. The second industrial revolution related to electricity, the third computerized industrial revolution. 4.0 industrial revolutions marked the development of technology and information that is very extraordinary.In the era of the Industrial Revolution 4.0, students must be brave enough to get out of their comfort zone. Studying in college is not only directed to the level of being (learning to find identity), to know (learning to know), and to do (applying knowledge to real life) but more than that reaching to live together (learning to form life attitude in togetherness).In the era of Industrial Revolution 4.0 Universities are required to graduate students who have adaptive abilities to changes that occur more frequently. These capabilities include the ability to solve problems that are increasingly complex, think critically, creatively, be able to become good managers, and have good coordination skills. College graduates are also expected to have good emotional intelligence, the ability to appraise and decide appropriately, be service-oriented, good at negotiation and flexible cognitive power.